Multi-targeted nanogel drug delivery system alleviates neuroinflammation and promotes spinal cord injury repair - Penghui Wang; Zaifeng Chen; Ping Li; Abdullah Al Mamun; Shaoxia Ning; Jinjing Zhang; Chonghui Tang; Tianmiao Sun; Jian Xiao; Xiaojie Wei; Fenzan Wu (Materials Today Bio)
Spinal cord injury (SCI) is significantly hampered by an inflammatory microenvironment, prompting continued efforts in drug development to address inflammation. Research shows that quercetin (Que) exhibits excellent performance in reducing inflammation and neuroprotection. However, its application is limited by poor solubility, notable side effects, and the unique pathophysiology of the spinal cord. In this study, we introduce a novel multifunctional liposome hydrogel drug delivery system (QLipTC@HDM), obtained by incorporating liposomes with blood-spinal cord barrier penetration and injury site targeting properties (LipTC) into a dual-network viscous hydrogel (HDM). Our results demonstrate that encapsulating Que in LipTC (QLipTC) enhances solubility, minimizes toxic side effects, facilitates lesion targeting, and aids in crossing the blood-spinal cord barrier. Moreover, encapsulation in HDM significantly prolongs the retention of QLipTC at the injury site after local administration. Crucially, our findings reveal that QLipTC@HDM induces M2 phenotype transformation in glial cells and in mice with SCI, thereby mitigating inflammation. This intervention additionally preserves the integrity of the blood-spinal cord barrier, optimizes the spinal cord microenvironment, reduces glial scarring, promotes axonal regeneration, and enhances motor function recovery in SCI mice. In summary, our investigations highlight the potential of this disease-specific drug delivery system as a promising therapeutic approach for the treatment and management of SCI.